Virtual Environments and Gender-Based Violence: Special Reference to the Metaverse and ChatGPT - Ricoy Casas, Rosa María; Fernández-González, Raquel; Santos-Garrido, Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Technologies such as the Metaverse or ChatGPT have incorporated gender-based violence into virtual spaces, reproduction of traditional sexist violence. Through a bibliographic review in the main scientific databases, their favorable conditions, characteristics, types of violence, examples of specific situations, scarce public policies and the very little interest on the part of the scientific community to address these issues, despite their radical importance, and the demand for international consultation to provide frameworks and protocols that can at least mitigate them due to the ubiquity of the Internet and the relocation of these companies.